2011
DOI: 10.1002/j.2161-1882.2011.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Responding to the Career Counseling Needs of International College Students on U.S. Campuses

Abstract: The authors believe that international students, increasingly visible on U.S. campuses, tend to confront unique career development challenges and often experience heightened vocational difficulty. In this article, the authors present 3 themes regarding international students' career needs derived from the current literature: career placement needs, individual factors mediating international student career needs and barriers, and help-seeking behaviors. Implications for college counseling professionals and sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 38 publications
(73 reference statements)
0
43
1
2
Order By: Relevance
“…Mulheres mães privadas de liberdade apresentam necessidades relacionadas à educação continuada e treinamento vocacional (Laux et al, 2011). Estudantes universitários estrangeiros demandam estratégias para colocação professional, para lidar com fatores individuais que interferem nas barreiras percebidas na carreira e estratégias para busca de ajuda (Crockett & Hays, 2011). A partir dessas evidências, verifica-se que pessoas que compõem grupos diferentes apresentam demandas de carreira diferentes.…”
Section: Público-alvounclassified
“…Mulheres mães privadas de liberdade apresentam necessidades relacionadas à educação continuada e treinamento vocacional (Laux et al, 2011). Estudantes universitários estrangeiros demandam estratégias para colocação professional, para lidar com fatores individuais que interferem nas barreiras percebidas na carreira e estratégias para busca de ajuda (Crockett & Hays, 2011). A partir dessas evidências, verifica-se que pessoas que compõem grupos diferentes apresentam demandas de carreira diferentes.…”
Section: Público-alvounclassified
“…While scholars agree that the level of acculturation impacts the experience international students have in navigating their career development in the U.S., a variety of approaches have been taken to explore the impact. Research shows that students who have reached a higher level of acculturation are better able to assess their career development needs than those who exhibit lower acculturation levels (Baruch, Budhwar, & Khatri, 2007;Crockett & Hays, 2011;Heggins & Jackson, 2003). This is supported by the research of Reynolds and Constantine (2007) who studied 261 international college students from Africa, Asia, and Latin America, and found that higher levels of acculturation stress lead to lower levels of career outcome expectations.…”
Section: Acculturation Factorsmentioning
confidence: 99%
“…International students come to study in the U.S. with a unique set of needs and expectations that include stressors above and beyond the common challenges generally experienced by college students (Crockett & Hays, 2011;Leong & Sedlacek, 1989;Reynolds & Constantine, 2007;Tidwell & Hanassab, 2007). To better understand these needs and expectations, it is important to consider the acculturation factors that influence the experiences of international students.…”
Section: International Student Needs and Expectationsmentioning
confidence: 99%
See 2 more Smart Citations